Machine-based Intelligent Face Recognition - Mou, Dengpan (Springer Berlin / Heidelberg, 2011)
This book discusses the general engineering method of imitating intelligent human brains for video-based face recognition in a fundamental way. It overviews state-of-the-art research on this subject, and especially the advances in face recognition.